1964
DOI: 10.1073/pnas.51.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms for Synthesis of Capsular Polysaccharide in Mucoid Mutants of Escherichia Coli K12

Abstract: Jacob and Monod have proposed that regulator genes may control the syntheses of several related enzymes in Escherichia coli K12.1 The present paper provides evidence for a regulator gene (designated R1)2 which controls capsular polysaccharide synthesis in E. coli K12. Certain mutants of E. coli produce large mucoid colonies which are characterized by overproduction of polysaccharide. The polysaccharide from such mucoid mutants of E. coli strain W contains galactose, fucose, and uronic acid.3 Serological studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
114
1
1

Year Published

1968
1968
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 27 publications
6
114
1
1
Order By: Relevance
“…(1 97 I), Markovitz (1964) and Broda (1974), respectively. In the reciprocal transduction (Table 3), selection was made for hem-361+ transductants on GMA containing proline and 5-ALA. Tests for cotransduction with hem-361f of proC and lac Y+ were made by restreaking each hem-361' transductant on glucose minimal medium (with 5-ALA), and on lactose minimal medium (with 5-ALA and proline).…”
Section: Haemin-requiring Mutantsmentioning
confidence: 99%
“…(1 97 I), Markovitz (1964) and Broda (1974), respectively. In the reciprocal transduction (Table 3), selection was made for hem-361+ transductants on GMA containing proline and 5-ALA. Tests for cotransduction with hem-361f of proC and lac Y+ were made by restreaking each hem-361' transductant on glucose minimal medium (with 5-ALA), and on lactose minimal medium (with 5-ALA and proline).…”
Section: Haemin-requiring Mutantsmentioning
confidence: 99%
“…This enzyme is a serine protease with an essential ATPase activity (37) and seems to be a heat shock protein (25). Ion mutations in E. coli result in pleiotropic phenotypes such as increased sensitivity to UV irradiation (10,16) and SOS-inducing agents (35), abnormal cell division (filament formation [16]), mucoid formation (12,22), defective lysogeny of phages A and P1 (32,36), and reduced degradation of various abnormal proteins (13) and certain normal proteins. Various observations indicate that protease La catalyzes rate-limiting steps in the degradation of some regulatory proteins such as SulA and RcsA (23,34).…”
mentioning
confidence: 99%
“…2 Independent experiments of Howard-Flanders, Simson, and Theriot,4 and Adler and Hardigree5 demonstrated that a mutation designated lon-caused E. coli K12 to become very sensitive to ultraviolet (UV) and ionizing radiation. These lon-strains are mucoid4 and after X-ray radiation form filaments that die.5 It is now clear that the phenotype of capR and lon mutants are identical, i.e., mucoid and UV sensitive," 2, 4-7 and arise from the same mutational event.…”
mentioning
confidence: 99%
“…2 3 8 The sugar components of the capsule are D-glucose, D-galactose, D-glucuronic acid, and L-fucose." 2 Independent experiments of Howard-Flanders, Simson, and Theriot,4 and Adler and Hardigree5 demonstrated that a mutation designated lon-caused E. coli K12 to become very sensitive to ultraviolet (UV) and ionizing radiation. These lon-strains are mucoid4 and after X-ray radiation form filaments that die.…”
mentioning
confidence: 99%